An investigation of the sustainability of the Imbewu Project at Phiwe Primary School - Maselana, Thobeka (Rhodes University, Faculty of Education, Department of Education, 2007)
Sustainable development and projects are relatively new terms In the South African context. This study explores these concepts as they relate to a school that is piloting a project in the Eastern Cape. A number of projects have been introduced in disadvantaged schools to redress imbalances of the past. Funders invest a lot of money, but when they leave, schools struggle to sustain these initiatives. This study aims to investigate whether the Imbewu Project, an educational development pilot project meant to improve schools in the Eastern Cape, made provision for long-term sustainability and whether the school sustained the project. Very little research seems to have been conducted on sustainability, especially in South Africa (SA). The study is conducted in the interpretive paradigm. A single case study involving a number of stakeholders at Phiwe Primary School (PPS) was conducted through observations, interviews, focus groups and document analysis. The study found that the action research strategy intended for the project was constrained by the limited time allowed. In addition, the approach did not address processes which are important for sustainability. Also, the cascade approach to learning is not successful in organisations that have not reached the status of being learning organisations. PPS is still struggling to change its culture and therefore one can say that they cannot sustain the changes that are brought by the project. Firstly, they did not involve the parents in most modules as the project suggested. Secondly, some facilitators did not understand the project. Thirdly, although the project provided for monitoring and support, the study found that there was inadequate support from the project team and district officials. There was a shortage of district officials because the Eastern Cape Department of Education did not invest in appointing people that could sustain the project. However, there are areas where the school is doing an outstanding job despite the fact that there was very little support. The school performed well in implementing and sustaining the project in the following areas: learner welfare, community involvement and involvement of staff members in committees.
Keywords: Education -- South Africa -- Eastern Cape; Sustainable development -- South Africa -- Eastern Cape; Project method in teaching -- South Africa -- Eastern Cape; School improvement programs -- South Africa -- Eastern Cape -- Case studies; Educational change -- South Africa -- Eastern Cape; Education and state -- South Africa -- Eastern Cape